С новым годом!: стихи малышам : (0+) / [редактор Т. Рашина] - Рашина Т. (Любимые сказки малышам, 2014)
Экземпляры: чзд (20151012) / Инвентарный номер: 059558 / Цена: 145.00 / Авт.знак: С 11 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6